STRATEGI PEMASARAN CITILINK DALAM MEMENANGKAN PERSAINGAN DI PASAR INDONESIA - Imam Ozali; Charles AN; Yana Tatiana (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
The Indonesian domestic aviation industry continues to experience significant growth in line with increasing public mobility and expanding regional access. Citilink, a subsidiary of Garuda Indonesia operating as a low-cost carrier (LCC), strives to strengthen its national market share through the implementation of adaptive and innovative marketing strategies. This study aims to analyze Citilink's marketing strategy to win the Indonesian domestic aviation market competition in 2024. Using a qualitative approach and descriptive methods, data were collected through interviews with Citilink management, observations in various operational areas, and secondary document reviews. The results show that Citilink consistently applies the marketing mix (7Ps) covering product, price, place, promotion, people, process, and physical evidence. Competitive pricing strategies, aggressive digital promotional campaigns, and collaboration with various industrial sectors and local governments are key to expanding market reach. Citilink positions itself as a